Faktor-Faktor Penghambat Keterlaksanaan Kurikulum 2013 pada Kompetensi Keahlian Teknik Fabrikasi Logam di SMK - Muhammad Sholeh Ridho; Sentot Wijanarka (Department of Mechanical Engineering Education, 2016)
The purpose of the research was to describe the many factors which pose as obstacles in the implementation of the 2013 curriculum in the TFL skills competency at SMK N 1 Seyegan Sleman Yogyakarta. These factors include teacher, infrastructure, lesson material and student. This research is a qualitative descriptive research. Data were collected by means of observation, interview and document analysis. Data were analyzed using the Miles and Huberman's interactive model which includes presentation of data, reduction of data, and conclusion. Result shows that factors which pose as obstacles to implementing the 2013 curriculum can be viewed from several aspects: In the aspect of teachers, there is lack of socialization and lack of readiness of teachers. In infrastructure aspects, equipment do not meet the standards, and lack of workshop space, lack of safety equipment, many types of equipment had worn out, and lack of blank material for practice. In the aspect of teaching materials, there are no teaching materials or special module for TFL skills competency. In the aspect of students, obstacles are the long class hours, and inadequate equipment and tools leaving the students become unproductive.———————————————————————————-Penelitian ini bertujuan mendeskripsikan faktor-faktor yang menghambat keterlaksanaan kurikulum 2013 pada kompetensi keahlian TFL di SMK N 1 Seyegan Sleman Yogyakarta meliputi aspek guru, sarana prasarana, bahan ajar serta peserta didik. Penelitian ini merupakan penelitian deskriptif kualitatif. Teknik pengumpulan data mengggunakan observasi, wawancara dan pencermatan dokumen. Analisis data menggunakan model interaktif Miles dan Huberman meliputi penyajian data, reduksi data, dan penarikan kesimpulan. Hasil penelitian adalah Faktor-faktor yang menghambat keterlaksanaan kurikulum 2013 dilihat dari beberapa aspek yakni; dari aspek guru ialah kurangnya kegiatan sosialisasi dan kurangnya kesiapan guru. Pada aspek sarana prasarana ialah peralatan praktik belum memenuhi standar, kurangnya ruang bengkel, belum lengkapnya perlengkapan keamanan, peralatan sudah banyak yang telah usang, serta kurangnya bahan untuk praktik. Pada aspek bahan ajar ialah belum adanya bahan ajar/modul khusus pada kompetensi keahlian TFL. Pada aspek peserta didik ialah jumlah jam pelajaran yang bertambah panjang.